Dimethyl sulfoxide: a central player since the dawn of cryobiology, is efficacy balanced by toxicity - Awan, Maooz; Buriak, Iryna; Fleck, Roland; Fuller, Barry; Goltsev, Anatoliy; Kerby, Julie; Lowdell, Mark; Mericka, Pavel; Petrenko, Alexander; Petrenko, Yuri; Rogulska, Olena; Stolzing, Alexandra; et al. (Regenerative medicine, 2020)
Dimethyl sulfoxide (DMSO) is the cryoprotectant of choice for most animal cell systems since the early history of cryopreservation. It has been used for decades in many thousands of cell transplants. These treatments would not have taken place without suitable sources of DMSO that enabled stable and safe storage of bone marrow and blood cells until needed for transfusion. Nevertheless, its effects on cell biology and apparent toxicity in patients have been an ongoing topic of debate, driving the search for less cytotoxic cryoprotectants. This review seeks to place the toxicity of DMSO in context of its effectiveness. It will also consider means of reducing its toxic effects, the alternatives to its use and their readiness for active use in clinical settings.
Keywords: Cell Survival; Cryoprotective Agents; Tissue Engineering; kryoprezervace; kryoprotektivní látky; dimethylsulfoxid; Animals; Humans; Cryopreservation; Cryobiology; kryobiologie; lidé; tkáňové inženýrství; zvířata; Dimethyl Sulfoxide; viabilita buněk